Army Corps Mega Projects Benefits From Innovative Foundations - Dale Berner; Michael O’Sullivan (Deep Foundations Institute, 2017)
"This paper focuses on lessons learned from the innovative designs, in-the-wet construction methodology and modified foundation conditions, for two United States Army Corps of Engineers, USACE, Megaprojects:(a) The over $2 Billion Olmsted Dam across the Ohio River for the Louisville District; and(b) The $1.75 Billion Inner Harbor Navigation Canal, IHNC, Lake Borgne Hurricane Barrier in New Orleans for the Hurricane Protection Office, and the New Orleans District.Design innovations for the 24-inch dia. pipe pile foundation for the Olmsted Dam project include: (i) the use of controlled-fixity moment connections to the dam monoliths in order to tune the response of the dam under the 8.3 Richter scale seismic Maximum Credible Event, MCE; (ii) soil densification to inhibit liquefaction potential and (iii) design to facilitate underwater construction in a river with a highly moveable sand bed.Design innovations for 66-inch dia. concrete cylinder piles for the IHNC floodwall include: (i) the use of soil structure interaction, SSI, analyses to verify capacity to resist deep-seated failure plane in soft soil, while limiting lateral deflections to acceptable limits; (ii) the use of geo-fabric and scour stone for enhanced foundation response and (iii) design for ""in-the-wet"" construction on a fast-track basis.LESSONS LEARNED FROM THE INNOVATIVE OLMSTED DAM FOUNDATIONThe over $2Billion Olmsted Dam on the Ohio River is currently under construction 16 miles upstream from the confluence with the Mississippi River. It will consist of an 800-foot-long tainter gate section, a 1,400-foot navigable pass, two boat abutment sections, a fixed weir section, and upstream and downstream scour protection. The Olmsted Dam and its two, 1,200-foot locks, which were built in 2002, will eventually replace both Locks and Dam #52 and #53, both built in 1929, and thereby bring significant benefits to the Ohio River navigation system.In 2002, the Jacobs/COWI JV completed the design of the dam; which was an engineering challenge for several reasons, including:(a) Its proximity to the New Madrid Fault, could impose an 8.4 Richter Scale seismic event on the structure, which is located in an area of potentially liquefiable alluvium. The extensive seismic analysis performed by COWI included a response spectra analyses; lateral pushover analyses of pile foundations; hydrodynamic added masses; pile group effects; and the development of kinematic motions as a result of the soil-pile-structure interaction.(b) Maintaining vessel traffic along the river and accommodating fluctuating river elevations between 30-40 ft annually, and as much as 60 ft in a 100-year period.(c) Designing for the scour and uplift forces of artesian ground water and preserving a wildlife sanctuary on the Southern shore at the dam site."